High maternal haemoglobin and its relation to pregnancy induced hypertension - S., Manjunatha; Bennal, Amruta S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induced hypertension (PIH) is poorly understood condition of human pregnancy. It is a pregnancy specific disorder that can affect virtually every organ system. Exact cause is not known, thought to be multifactorial. The underlying pathology is endothelial dysfunction and intensive vasospasm, affecting almost all vessels. The responsible agent for dysfunction and vasospasm, still not been isolated precisely. So we have done the study to know the association of first trimester, high maternal haemoglobin with occurrence of PIH. Methods: The longitudinal study was conducted in the 400 pregnant women, who were enrolled in first trimester of pregnancy and followed till the delivery, with 200 pregnant women with haemoglobin >13gm% as cases and 200 pregnant women haemoglobin 11 to 13 gm% as controls. Statistical analysis was done by using Chi-square test. Results: The pregnant women with higher haemoglobin concentration in first trimester had higher risk of developing pre-eclampsia (PIH) comparing to other pregnant women (p <0.0001). Conclusions: High haemoglobin concentration in first trimester of pregnancy can be considered as risk factor Pregnancy induced hypertension.